Estudo da polarização quântica e do emaranhamento de estados coerentes de fótons adicionados - Nogueira, Keuliane da Silva (2012)
Polarization has been used extensively in quantum information processing, and quantum entanglement is essential to many areas of research, including quantum computing. Here we investigate the degree of polarization and the entanglement of a family of quantum states known as photon-added entangled coherent states. Such states could serve as means of entanglement distribution and quantum key distribution. Using the quantum Stokes parameters and the Q function, we demonstrated that, in general, the polarization of a superposition of two two-mode photon-added coherent states increases significantly with the number of added photons. And using the concurrence, we showed that the amount of entanglement in this kind of superposition presents a behavior that is dependent on whether or not the number of added photons on each mode is the same.